Three mountains and seven rivers : Prof. Musashi Tachikawa's felicitation volume - Tachikawa, Musashi; Hino, Shoun; Wada, Toshihiro (Delhi : Motilal Banarsidass Publishers, 2004)
Contributed articles on miscellaneous Indological topics.
Sadrži bibliografske bilješke
Keywords: indijska filozofija - razne teme; indijske religije - razne teme; indijska filologija